Determination of Employee Managerial Performance at Ground Handling Company - Aviyanti, Cut (Dinasti Publisher, 2024)
This study aims to explore the influence of motivation, resilience, and work-life balance on employee managerial performance in ground-handling companies. Utilizing a mixed-method research approach, quantitative data will be gathered through surveys, while qualitative insights will be obtained via semi-structured interviews. Statistical and thematic analyses will be conducted to understand the impact of these variables. Despite their perceived importance, our research suggests that the effects of motivation, resilience, and work-life balance on managerial performance may be less significant than assumed. Further investigation is required to comprehend the complex interplay of factors contributing to effective managerial performance in organizational contexts.